An Evaluation of Transition Planning for High School Students with Emotional and/or Behavioral Disorders (EBD) - Nylund, Amy (My University, 2009)
This study examined the views of high school students with Emotional and/or Behavioral Disorders (EBD) regarding the effectiveness of services provided by their school to help them prepare to transition from the school environment to post-school life, and their self-reported readiness for this transition.
Color poster with text and graphs describing research conducted by Any Nylund, advised by Marie K. Crothers.
Keywords: Adjustment disorders--Treatment--Evaluation; High school students--Services for--Evalutation; People with social disabilities--Services for--Evaluation; People with social disabilities--Life skills assessment; Posters